Evaluasi Kurikulum Pembelajaran Bahasa Arab di STAI Attanwir Bojonegoro - Khoirul Faizin (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2020)
Language learning is the most unique part of learning, especially foreign languages ??as learning and in this language is Arabic. The curriculum in a learning is very influential on the level of success of students. This study examines Arabic in terms of curriculum, because researchers consider this very important for the continuity of learning foreign languages, especially Arabic so that learning can be carried out optimally and optimally. In this case the researchers conducted research at one of the tertiary institutions in Bojonegoro namely STAI Attanwir. The researcher found that there were several elements in the language learning curriculum that had to be improved, among others, from the learning media and textbooks, as well as the learning system that caused students to not be able to receive lessons to the maximum. This happened because of the different backgrounds of Arabic learning students so that Arabic learning materials could only be understood by some students.